Cover Picture: A Phosphine‐Catalyzed Regioselective [3+2] Cycloaddition of Ethyl 5, 5‐Diarylpenta‐2, 3, 4‐trienoate with Aromatic Aldehydes and α, β‐Unsaturated Carbonyl Compounds (Adv. Synth. Catal. 16/2014). Issue 16 (3rd November 2014) - Wang, Lu‐Feng; Cao, Xiao‐Ping; Shi, Zi‐Fa; An, Peng; Chow, Hak‐Fun
<x xml:space="preserve">Abstract</x> The front cover picture, provided by Xiao‐Ping Cao, Zi‐Fa Shi and co‐workers, illustrates the double regioselective reaction pathways in the cycloaddition reactions of aromatic aldehydes and α, β‐unsaturated carbonyl compounds with ethyl 5, 5‐diphenylpentatrienoate on the background of the double water wheels of the Yellow River in Lanzhou, China. Details can be found in the full paper on pages 3383–3390 (L.‐F. Wang, X.‐P. Cao, Z.‐F. Shi, P. An, H.‐F. Chow, Adv. Synth. Catal. 2014, 356, 3383–3390; DOI: 10.1002/adsc.201301000).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>